Gestão das águas na comunidade quilombola da Serra do Evaristo, Baturité - Ceará - Pereira, Gino (2016)
Water resources are essential to all species survival, although environmental damages caused by human development are reducing the quality and availability of these resources. In rural properties these damages are mainly related to agricultural activities. The Quilombo Commuty of Evaristo, as well as other communities in Baturité city, it is characterized by the presence of small farms, developing focused agriculture in the production of banana and small livestock. In these places, the water used for human consumption, domestic use, animal consumption and production backyards comes strands, natural springs, ponds and tanks, which are managed by their owners. Thus, this work aims to analyze the management and ways to capture and storage of water in the community to an understanding in more detail, how is the management of process water in the community. The methodology of this qualitative study involved the semistructured interviews conducted individually, a meeting with a young group and two meetings with community leadership, in addition to literature review was conducted workshops themed facing environmental education. he survey revealed the following results: there is a water management with concern in the community, the more the community is not organized to do so; water demand and outstripping supply; abandonment of natural sources that could be meeting some needs of the residents if they were maintained; most community decisions are made at the general meeting by; low participation of young people in the association meetings; lack of care at the time of collection of rainwater; poor quality of the water consumed in the community. The conclusion is that the community is in the process of construction between among residents, mostly through informal conversations face to face. Even being aware of the lack of water problems that occur in the community, do not mobilize for an awareness campaign for the use and management of their water.